Second row: Dankert behind flag and Lulling at his right. First row: f.l.t.r. Renger, Dingels (Mrs), Dingels (Mr) and Nau
Second row: Dankert behind flag and Lulling at his right. First row: f.l.t.r. Renger, Dingels (Mrs), Dingels (Mr) and Nau.